2009
DOI: 10.1021/jm900933k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Selective H1-Antihistamines for Clinical Evaluation in the Treatment of Insomnia

Abstract: Analogues of the known H(1)-antihistamine R-dimethindene were profiled as potential agents for the treatment of insomnia. Several highly selective compounds were efficacious in rodent sleep models. On the basis of overall profile, indene 1d and benzothiophene 2a had pharmacokinetic properties suitable for evaluation in night time dosing. Compound 2a did not show an in vivo cardiovascular effect from weak hERG channel inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…The cross-coupling reaction was found to proceed in good yield and excellent stereospecificity to give 57 , which was further elaborated over 3 steps to produce 58 , an H 1 antihistamine shown to have anti-insomnia properties. xxxvii An enantioenriched anticancer agent was also synthesized using our cross-coupling method. xxxviii …”
Section: Stereospecific Reactionsmentioning
confidence: 99%
“…The cross-coupling reaction was found to proceed in good yield and excellent stereospecificity to give 57 , which was further elaborated over 3 steps to produce 58 , an H 1 antihistamine shown to have anti-insomnia properties. xxxvii An enantioenriched anticancer agent was also synthesized using our cross-coupling method. xxxviii …”
Section: Stereospecific Reactionsmentioning
confidence: 99%
“…1 A highly efficient and direct route to these valuable chiral compounds is the metal-catalyzed cross coupling of a benzylic electrophile with an organometallic reagent. 2 Such couplings have been accomplished in both enantioselective and enantiospecific fashion.…”
mentioning
confidence: 99%
“…1 These valuable targets can be prepared via cross couplings of classic electrophiles, such as benzylic halides, with Grignard, organozinc and organoboron reagents. 2 In fact, Carretero has shown that enantioenriched diarylethanes can be formed via stereospecific cross couplings of benzylic bromides with aryl Grignard reagents (Scheme 1A-1).…”
mentioning
confidence: 99%
“…We established the absolute configuration of diarylethane 35 , whose racemate displays anti-cancer activity, 1d, e by comparison of its optical rotation to the reported value. 5b The absolute configuration of ( R )- 38 was determined by X-ray crystallography (Figure 1).…”
mentioning
confidence: 99%